Sulfur-driven switching of the Ullmann coupling on Au(111). Issue 29 (26th March 2018) - Rodríguez-Fernández, Jonathan; Schmidt, Søren Birthin; Lauritsen, Jeppe V.
Abstract : We demonstrate the inhibition and reactivation of the Ullmann coupling reaction by molecular gases. Abstract : We demonstrate a method to selectively switch the Ullmann coupling reaction of 2, 8-dibromodibenzothiophene on a Au(111) support. The Ullmann coupling reaction is effective already at low temperature, but the complete inhibition of the same reaction can be achieved on Au(111) pre-exposed to H2 S. The marked difference in reactivity of pretreated Au(111) is explained by the S-passivation of free Au atoms emerging from reconstruction sites. The inhibited state can be fully lifted by removing the S via hydrogen gas post-exposure.